Epigallocatechin gallate inhibits release of extracellular vesicles from platelets without inhibiting phosphatidylserine exposure - Sarah L. Millington-Burgess (Nature Portfolio, 2021)
Abstract Arterial thrombosis triggers myocardial infarction and is a leading cause of death worldwide. Procoagulant platelets, a subpopulation of activated platelets that expose phosphatidylserine (PS), promote coagulation and occlusive thrombosis. Procoagulant platelets may therefore be a therapeutic target. PS exposure in procoagulant platelets requires TMEM16F, a phospholipid scramblase. Epigallocatechin gallate (EGCG) has been reported to inhibit TMEM16F but this has been challenged. We investigated whether EGCG inhibits PS exposure in procoagulant platelets. PS exposure is often measured using fluorophore-conjugated annexin V. EGCG quenched annexin V-FITC fluorescence, which gives the appearance of inhibition of PS exposure. However, EGCG did not quench annexin V-APC fluorescence. Using this fluorophore, we show that EGCG does not inhibit annexin V binding to procoagulant platelets. We confirmed this by using NBD-labelled PS to monitor PS scrambling. EGCG did not quench NBD fluorescence and did not inhibit PS scrambling. Procoagulant platelets also release PS-exposing extracellular vesicles (EVs) that further propagate coagulation. Surprisingly, EGCG inhibited EV release. This inhibition required the gallate group of EGCG. In conclusion, EGCG does not inhibit PS exposure in procoagulant platelets but does inhibit the EV release. Future investigation of this inhibition may help us further understand how EVs are released by procoagulant platelets.